DIAGNOSTICS AND TREATMENT HEPATOPATHY OF THE DOGS FOR BABESIOSIS - Горальська, І. О. (Scientific Progress & Innovations, 2014)
Dogs which are suffering from babesiosis , at different stages of disease pathology installed liver (hepatopathy), which is characterized by pain in the liver area of the field, hepatomegaly, ikterychnistyu conjunctiva, hypoalbuminemia, hyperbilirubinemia, increased activity of ALT, AST and GGT. Three-week course of treatment for babesiosis of dogs with signs of jaundice using glucose, ascorbic acid, glutargin, contrical, katozalu, panangin, lasix and essentiale forte leads to a gradual, partial recovery of the functional state of the liver.